2010
DOI: 10.1073/pnas.1013105107
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic processing of protocadherin proteins requires endocytosis

Abstract: The α-, β-, and γ-protocadherins (Pcdhα, Pcdhβ, and Pcdhγ) comprise a large family of single-pass transmembrane proteins predominantly expressed in the nervous system. These proteins contain six cadherin-like extracellular domains, and proteolysis of Pcdhα and Pcdhγ by the γ-secretase complex releases their intracellular domains into the cytoplasm where they may function locally and/ or enter the nucleus and affect gene expression. Thus, cleavage of Pcdhs may function to link intercellular contacts and intrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 43 publications
1
34
0
Order By: Relevance
“…The model assumes that this large assembly then produces a signal for the two cells to move apart, with the assembly itself likely destroyed by proteolysis. In fact, the clustered Pcdhs have been shown to be cleaved by a metalloprotease and γ-secretase during development [45, 6365]. In contrast, when neurites from different neurons come into contact, there will be a high probability of at least one mismatched isoform which is enough to limit assembly size, and no repulsion signal will be produced.…”
Section: Discussionmentioning
confidence: 99%
“…The model assumes that this large assembly then produces a signal for the two cells to move apart, with the assembly itself likely destroyed by proteolysis. In fact, the clustered Pcdhs have been shown to be cleaved by a metalloprotease and γ-secretase during development [45, 6365]. In contrast, when neurites from different neurons come into contact, there will be a high probability of at least one mismatched isoform which is enough to limit assembly size, and no repulsion signal will be produced.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the γ-secretase-dependent cleavage of Pcdhα requires endocytosis. There were also suggestions that in this case, endocytosis of Pcdhα, extracellular domain cleavage, γ-secretase cleavage, and ESCRT-dependent trafficking maybe co-regulated during differentiation (Buchanan et al 2010). Interestingly, the endosomal sorting complex (ESCRT) also directs Notch-positive endosomes to the multivesicular body pathway and the lysosome (Vaccari et al 2008).…”
Section: The Role Of the Gamma-secretase Complex: Beyond The Beaten Tmentioning
confidence: 97%
“…An elegant example linking: γ-secretase cleavage, signaling and endocytosis, is the proteolytic processing of protocadherin proteins (Pcdh; Buchanan et al 2010). Protocadhedrins are single-pass transmembrane proteins predominantly expressed in the nervous system.…”
Section: The Role Of the Gamma-secretase Complex: Beyond The Beaten Tmentioning
confidence: 99%
“…Like the classic cadherins, Pcdhs are glycoproteins with N-linked glycan sequons located in their extracellular domains. Studies have shown that Pcdhs are proteolytically cleaved by ␥-secretase complex, producing soluble intracellular fragments that may enter the nucleus and affect gene expression (41,42). Of note, several studies have shown that the Pcdh superfamily may be implicated in tumor development and function as tumor suppressors.…”
Section: Discussionmentioning
confidence: 99%